Maternal exposure to TCDD during gestation advanced sensory-motor development, but induced impairments of spatial learning and memory in adult male rat offspring. (December 2018) - Zhang, Hua-jing; Liu, Ya-nan; Xian, Ping; Ma, Jing; Sun, Ya-wen; Chen, Jing-shan; Chen, Xi; Tang, Nai-jun
Abstract: 2, 3, 7, 8-Tetrachlorodibenzo-p-Dioxin (TCDD) is an endocrine disrupting chemical (EDC) with high persistency. Even a low amount can pass the placental barrier during gestational exposure. Exposure to TCDD exposure can impair the development of the nervous system in children, leading to impaired learning ability in later-life. But the changes in neurobehavioral developments in infancy and childhood caused by TCDD are unknown. Pregnant Sprague-Dawley rats were given a consecutive daily dose of TCDD (200 or 800 ng/day/kg) or an equivalent volume of vehicle by gavage on gestational days 8–14 (GD 8–14) as the prenatal TCDD exposure model. In the offspring, early neurobehavioral development was assessed at postnatal day 5 (PND5) and eye-opening was monitored from PND10 onwards. Adult male offspring was tested by Morris Water Maze for spatial memory and learning ability evaluation. Hippocampus Nissl's staining and astrocyte GFAP immunohistochemistry were used to evaluate the activity of astrocytes. The results of the behavioral tests showed that gestational TCDD exposure induced premature motor activity and earlier eyes-opening, but lead to serious deficits of spatial memory and learning ability in the adult male offspring. Morphology and number of neurons in the hippocampus CA1 region was not affected, while the activity of astrocytes in the same region was significantly reduced. These data indicate that perinatal TCDD exposure induced premature neurobehavioral development but impaired the spatial learning and memory in adult male rat offspring. The decreased activity of astrocytes in the hippocampus may play a role in these adverse effects. Graphical abstract: Highlights: Perinatal exposure to TCDD advanced sensory-motor development in the early life stages of F1 male rats. Perinatal exposure to TCDD impairs the ability of spatial learning and memory in adulthood. The activity of hippocampal astrocytes in the adult male offspring was inhibited after perinatal TCDD exposure. The decreased activity of astrocyte may play a role in the impairment of the spatial learning and memory in adulthood.